FACTORS INFLUENCING STUDENTS' INTENTION TO ADOPT E-LEARNING WITH EXTENDED UTAUT - Purnomohadi Sutedjo, Sing Tjoen; Pramana, Edwin; Gunawan, Gunawan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the factors that influence students' intention to adopt e-learning in Surabaya, using a modified theoretical model of the Unified Theory of Acceptance and Use of Technology (UTAUT). Through a quantitative approach, data were collected from 489 respondents who had used e-learning, using a questionnaire distributed online. The results showed that Performance Expectancy, Effort Expectancy, and Learning Convenience had a significant influence on students' Behavioral Intention to use e-learning. Social Influence and Facilitating Conditions were proven to have no influence on Behavioral Intention. In addition, Educational Level acts as a moderating variable that strengthens the relationship between Learning Convenience and Behavioral Intention, with a stronger effect on postgraduate students. This study provides theoretical contributions by enriching the UTAUT study through the addition of new factors, as well as practical contributions for e-learning developers and educators in designing more effective and user-friendly platforms. These findings are expected to provide broader insights into the acceptance of e-learning across educational levels and geographic contexts.